A new fluorescence method for determination of ozone in ambient air - Felix, Erika P.; Passaretti Filho, Juliano [UNESP]; Garcia, Gabriel [UNESP]; Cardoso, Arnaldo Alves [UNESP] (Elsevier B.V., 2011)
A new simple method for determination of ozone in ambient air is presented. The reaction employed is based on the known ozonolysis of indigo dye. The indigotrisulfonate molecule contains one carbon-carbon double bond (C C), which reacts with ozone and generates isatinsulfonates and sulfoanthranilate. The quantitatively formed sulfoanthranilate presents fluorescence (lambda(ex) 245 nm, lambda(em) 400 nm). Ozone was collected using two cellulose filters coated with 40 mu L of 1.0 x 10(-3) mol L(-1) of indigotrisulfonate. The analytical response was linear in the range 0-150 ppbv ozone, and a detection limit of 7 ppbv was achieved using a sampling time of 15 min and an optimum sampling air flow rate of 0.4 L min(-1). There was no interference from sulfur dioxide, formaldehyde or nitrogen dioxide. The ozonolysis mechanism and the reaction products are discussed. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Ozone determination; Air analysis; Indigotrisulfonate; Ozonolysis; Fluorescence; Sulfoanthranilate